Convergent validity of actigraphy with polysomnography and parent reports when measuring sleep in children with Down syndrome. Issue 4 (5th January 2018) - Esbensen, A. J.; Hoffman, E. K.; Stansberry, E.; Shaffer, R.
Abstract: Background: There is a need for rigorous measures of sleep in children with Down syndrome as sleep is a substantial problem in this population and there are barriers to obtaining the gold standard polysomnography (PSG). PSG is cost‐prohibitive when measuring treatment effects in some clinical trials, and children with Down syndrome may not cooperate with undergoing a PSG. Minimal information is available on the validity of alternative methods of assessing sleep in children with Down syndrome, such as actigraphy and parent ratings. Our study examined the concurrent and convergent validity of different measures of sleep, including PSG, actigraphy and parent reports of sleep among children with Down syndrome. Method: A clinic ( n  = 27) and a community ( n  = 47) sample of children with Down syndrome were examined. In clinic, children with Down syndrome wore an actigraph watch during a routine PSG. In the community, children with Down syndrome wore an actigraph watch for a week at home at night as part of a larger study on sleep and behaviour. Their parent completed ratings of the child's sleep during that same week. Results: Actigraph watches demonstrated convergent validity with PSG when measuring a child with Down syndrome's total amount of sleep time, total wake time after sleep onset and sleep period efficiency. In contrast, actigraph watches demonstrated poor correlations with parent reports of sleep, and with PSG when measuring the total time in bed and total wake episodes. Actigraphy, PSG and parent ratings of sleep demonstrated poor concurrent validity with clinical diagnosis of obstructive sleep apnoea. Conclusion: Our current data suggest that actigraph watches demonstrate convergent validity and are sensitive to measuring certain sleep constructs (duration, efficiency) in children with Down syndrome. However, parent reports, such as the Children's Sleep Habits Questionnaire, may be measuring other sleep constructs. These findings highlight the importance of selecting measures of sleep related to target concerns.